2008
DOI: 10.1002/cncr.23541
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid fine-needle aspiration: Smears versus liquid-based preparations

Abstract: T he sampling of tissue with needles for the purpose of investigating neoplastic processes has been reported over the past 160 years. 1,2 Until recently, smears, sometimes in combination with cell blocks, have been the sole preparation technique for these samples. Likewise, the Papanicolaou (Pap) test, by far the most successful screening test for any cancer, was until approximately 10 years ago prepared exclusively as a smear.The screening of Pap smears by humans is a laborious process and is fraught with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…From this point on, liquid-based preparations (LBP) will be an alternative method. It is well known that LBP smears improve the quality of cytomorphology, devoid of obscuring elements, and preserve cells adequately [29]. A large-scale study evaluated the efficacy of thyroid FNA compared to LBP with conventional smears and confirmed the effectiveness of LBP for preoperative selection of thyroid neoplasms and decreasing indeterminate diagnoses [30].…”
Section: Discussionmentioning
confidence: 99%
“…From this point on, liquid-based preparations (LBP) will be an alternative method. It is well known that LBP smears improve the quality of cytomorphology, devoid of obscuring elements, and preserve cells adequately [29]. A large-scale study evaluated the efficacy of thyroid FNA compared to LBP with conventional smears and confirmed the effectiveness of LBP for preoperative selection of thyroid neoplasms and decreasing indeterminate diagnoses [30].…”
Section: Discussionmentioning
confidence: 99%
“…2 The low diagnostic accuracy of benign lesions on direct conventional smears has not commonly been observed in other studies. Amrikachi et al 13 found that only 3% of cases diagnosed as follicular neoplasms on FNA smears proved to be benign adenomatous nodules.…”
Section: Commentmentioning
confidence: 90%
“…126 A recent nationwide educational survey by the College of American Pathologists found a troubling approximately 40% of circulated FNA slides felt to represent FNs were miscategorized as either benign or malignant. 127 An overall 18% diagnostic discordance was found on review of thyroid FNAs referred to a tertiary care center.…”
Section: The Continuing Importance Of the Primary Cytologic Diagnosismentioning
confidence: 99%